Exploring First-Year EFL Students’ Problems in Essay Writing - Doni Alfaruqy; Harits Setyawan; Tefur Nur Rohman (Universitas Islam Negeri Raden Mas Said Surakarta, 2022)
Writing has been considered the most difficult skill to master by EFL university students. It needs more effort and time for mastery. Some challenges in writing can make students confused. This condition has inspired the researchers to conduct the study. The study aims to identify the common errors in first-year students’ essay writing and provide suggestive solutions for the problems encountered by the students. This study was implemented using quantitative and qualitative approaches (mixed method). The researchers analyzed 205 students’ essays to identify the writing errors. After that, they randomly interviewed selected students to find the specific problems and suggestions. The data gathered were then classified and analyzed thematically. Based on the analyzed data, the most frequent error was faulty sentences which was 60.41%, grammar as the second error was 16.88%, the third error was mechanics with 13.1%, and vocabulary and other errors were 5.38% and 4.22%. The result shows that most students got difficulty writing sentences correctly. Therefore, providing appropriate learning materials for students and giving feedback on their writing are suggested.